The Philippine journal of science Ichthyological papers from volume 3, 1908 through volume 87, no. 1, 1958. (T.F.H. Publications, 1969)
Contents : Articles 60-94, 1936-1958. v3. The sexual maturity of some commercial fishes caught in Manila Bay / P.R. Manacop -- A redescription of the genus Mirogobius Herre (Gobiidae) / H.A. Roxas and G.J Blanco -- Ecological studies on marine relicts and landlocked animals in inland waters of Nippon / D. Miyadi -- A new taenioid fish from Occidental Negros / H.A. Roxas and G.L. Ablan -- Two are Phil. fishes / C. Martin -- A review of Phil. Holocentridae / J.R. Montilla -- Studies on the anatomy of the bangus, Chanus chanus / D.S. Rabor -- Early life history of the vivaparous perch Taeniotoca lateralis Agassiz / G.J. Blanco -- Two rare pediculate fishes from the Phil, / A.G. Agco -- A new genus of labroid fishes / L.F. De Beaufort -- The Phil. blennies / A.W.C.T. Herre -- A new fish from Lingayen Gulf, Phil. / H.A. Roxas and G.L. Ablan -- A new gobioid fish from Luzon / H.A. Roxas and G.J. Blanco -- Two new Phil. gobioids / G.L. Ablan -- Notes on fishes in the Zoological Museum of Standard Univ. / A.W.C.T. Herre -- Phil. gobioid fishes / H.A. Roxas -- A review of Phil Carangidae / H.A. Roxas -- Studies on the Biology of the Amoy amphioxus, Branchiostoma belcheri / T.G. Chin -- Artificial fertilization and embryology of Mirogobius lacustris / G.J. Blanco -- The breeding activities and embryology of Aplocheilus luzonensis / G.J. Blanco -- Noteworthy addition to the Phil. fish fauna with description of new genus and species / A.W. Herre and E.S. Herald -- Six addition to the Phil. fish fauna, including two new specie / A.W. Herre -- A review of the scorpaenoid fishes of the Phil. and adjacent seas / A.W.C.T. Herre -- A new record of hemirhamphid from the Phil. / A.M. Sarenas and I.A. Ronquillo -- Eight additions to the Phil. fish fauna, including three new species / A.W.C.T. Herre -- Tropical Pacific gobies with vomerine teeth / A.W.C.T. Herre -- The tropical Pacific Eleotride with vomerine teeth with descriptions of two new genera and two new species from the Marshall Is. / A.W.C.T. Herre -- A new species of Gnatholoepis with a key to the tropical Pacific species / A.W.C.T. Herre -- The eleotrid gobies of the Phil Myctophidae / A.M. Serenas -- Discovery of living specimens and redescription of Pandaka Pygmaea / A.M. Serenas and L.A. Ronquillo -- The guitarfishs, family Rhinobathidae, of the Phil. and adjacent seas / A.W.C.T. Herre -- Marine Fishes in the Phil. rivers and lakes / A.W.C.T. Herre.